Hubungan Pengetahuan dan Pengambilan Keputusan Penggunaan Kontrasepsi Intra Uterine Device oleh Pasangan Usia Subur di Wilayah Kerja Puskesmas Poasia, Kota Kendari - Sarita, Sultina; Syahrianti, Syahrianti; Yustiari, Yustiari (Health Information : Jurnal Penelitian, 2021)
This study aims to determine the factors associated with the low participation of couples of childbearing age (PUS) in the use of Intra-Uterine Devices (IUD). Observational analytic research design with the cross-sectional method. And the research population is all PUS in the working area of ??the Poasia Health Center, the determination of the sample using the accidental method for PUS visiting the MCH/KB Polyclinic of the Poasia Health Center with a total sample of 43 respondents. The data were analyzed statistically using the chi-square test method. There are 14 respondents (32.5%) who have poor knowledge, 13 respondents (30.3%) have sufficient knowledge and 16 respondents (37.2%) have good knowledge about IUD contraception, in 22 respondents (51.3%) taking a decision in choosing the IUD contraception through discussion by husband and wife. There is a relationship between knowledge and low EFA participation in the use of IUD contraception (statistical test results, p-value 0.02). There is a relationship between decision-making and low EFA participation in the use of IUD contraceptives (statistical test results, p-value 0.04).